PERLINDUNGAN HUKUM BAGI KONSUMEN TERHADAP PEMBONGKARAN RUMAH DAN SERTIFIKAT YANG TIDAK SELESAI DALAM PEMBELIAN RUMAH SECARA KREDIT (Studi Kasus Jual Beli Rumah Di Cikarang) - Tia Monica Ifana; A.M Tri Anggraini (Jurnal Hukum Adigama, 2018)
Legal protection for consumers means all government efforts to ensure legal certainty to provide protection to its citizens so that their rights as a citizen is not violated, and for those who violate will be subject to sanctions in accordance with applicable regulations. consumer protection at this time can not be separated from trading activities, in trade activities such as housing construction is expected to create a balance of rights and obligations between business actors and consumers. but the housing scheme often involves some problems that can hurt the consumer housing industry, because there are still many developers who only seek profits as big as possible without thinking about the needs of consumers, with the rights of consumers who violated the need for legal protection and responsibility of the perpetrator business based on Article 19 UUPK. The research method used by the writer is normative research method supported by interview with resource person. A brief analysis of this journal is titled by the author. Conclusions and suggestions about the issues studied by the author.